Agricultural management for climate change adaptation, greenhouse gas mitigation, and agricultural productivity: Insights from Kenya - Bryan, Elizabeth; Ringler, Claudia; Okoba, Barrack; Koo, Jawoo; Herrero, Mario; Silvestri, Silvia (International Food Policy Research Institute, 2011)
Changes in the agriculture sector are essential to mitigate and adapt to climate change, ensure food security for the growing population, and improve the livelihoods of poor smallholder producers. What agricultural strategies are needed to meet these challenges? To what extent are there synergies among these strategies? This paper examines these issues for smallholder producers in Kenya. Several practices emerge as triple wins in terms of climate adaptation, GHG mitigation, and productivity and profitability. In particular, integrated soil fertility management and improved livestock feeding are shown to provide multiple benefits across the agroecological zones examined. In addition, irrigation and soil and water conservation are also shown to be essential in the arid zone. The results suggest that agricultural investments targeted towards triple-win strategies will have the greatest payoff in terms of increased resilience of farm and pastoralist households to climate change, rural development, and climate change mitigation for generations to come.